Comparison of diabetic and non-diabetic patients undergoing endovascular revascularization for peripheral arterial disease - Michael, S. Lee; Seung, Woon Rha; Seung, Kyu Han; Byoung, Geol Choi; Choi, Se Yeon; Ali, Jabar; Xu, Shaopeng; Ngow, Harris Abdullah; et al., (HMP Communications, 2015)
Peripheral arterial disease (PAD) is associated with poor outcomes. We assessed the clinical outcomes of diabetic versus non-diabetic patients with PAD who underwent peripheral transluminal angioplasty (PTA). The outcomes of 239 consecutive patients with symptomatic PAD who underwent PTA were analyzed. Restenosis and clinical outcomes were assessed at a follow-up of 2 years. Diabetic patients had a higher percentage of wound as the initial diagnosis for PTA (72.7% vs 14.2%; P<.001), chronic kidney disease (26.7% vs 6.3%; P<.01), need for dialysis (19.3% vs 3.1%; P<.01), and coronary artery disease (67.6% vs 50.7%; P=.02). Infrapopliteal PTA was more commonly performed in the diabetic group (70.4% vs 25.3%; P<.001). Diabetic patients had lower rates of angiographic follow-up at 8 months (38.6% vs 60.3%; P<.01). Diabetic patients had higher binary restenosis (54.4% vs 31.5%; P=.02) and had a trend toward a higher incidence of total occlusion (34.0% vs 19.5%; P=.08). At 2-year follow-up, the amputation rate was higher in the diabetic group (24.4% vs 1.5%; P<.001) despite PTA. Diabetic patients more frequently presented with critical limb ischemia compared with non-diabetic patients and had higher rates of restenosis and amputation at 2 years following standard PTA. Improved therapies are needed for this high-risk group of patients.